PELATIHAN PEMBUATAN ALAT PERAGA MOTOR LISTRIK SEDERHANA KEPADA SISWA DI SMA DARUSSALAM CIPUTAT - Faradiba (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM), Univesitas Kristen Indonesia, 2023)
The Physics Education Study Program is the only Physics Education Study Program in DKI Jakarta with the vision to implement learning using media made from simple materials. So that the Physics Education Study Program will apply the knowledge it has mastered to schools as a form of dedication and knowledge transfer. The Physics Education Study Program, FKIP UKI, conducted training on making simple electric motor teaching aids for students at Darussalam Ciputat High School, Tangerang. This training was carried out as an effort by the study program to implement expertise in community service activities. This activity will be carried out on Tuesday, September 6 2022, at Darussalam Ciputat High School, Tangerang. The programs carried out are: (1) Conducting outreach about science teaching aids that can be produced from used goods or simple materials that are easy to find; (2) Carry out practicum/experiments on props that have been made (electric motors); (3) Conducting learning by associating the concept of material with the results of experiments that have been carried out using the resulting teaching aids. This Community Service can be a means of increasing and developing the creativity of students and teachers in the learning process. Keywords: Simple electric motors, Students, SMA Darussalam Ciputat.